Compatibility of the Principles for Design of Thesaurus and Classification Scheme - Gopinath, M. A.; Prasad, K. N. (Journal of Information and Knowledge, 1976)
The performance of an Information Retrieval System can be improved by the use of controlled vocabularies, such as, classification schemes, subject authority lists, and theasuri. Recent trends in the field of design of different types of controlled vocabularies have developed exclusively, principles and rules for each one of these devices. While it is admitted that there are certain essential differences in each of these types of controlled vocabularies, there are also certain features which emphasize basic similarity, inter convertibility and compatibility among them. This paper discusses the compatibility of the guiding principles provided by the ISO for the construction of a thesaurus and the principles available in the General Theory of Library Classification. It is found that there are several initial steps which are common for construction of both a thesaurus and a classification scheme. The thesaurus usually con-fines itself to two planes of work, the idea plane and the verbal plane, whereas the classification system spreads into three planes off work, idea plane, verbal plane and the notational plane. The verbal plane of thesaurus actually takes some of the roles of the notational plane of a classification scheme. It is found that the role of thesaurus, classification scheme and that of a subject heading list can coexist and be used harmoniously in an integrated library and information system.